2017
DOI: 10.2147/jpr.s138147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of piroxicam for postoperative pain after lower third molar surgery associated with <em>CYP2C8*3</em> and <em>CYP2C9</em>

Abstract: ObjectiveNonsteroidal anti-inflammatory drugs (NSAIDs) are metabolized by the cytochrome P450 enzymes (CYPs), predominantly CYP2C8 and CYP2C9. The aim of this study was to evaluate the possible association of polymorphisms in the CYP2C8*3 and CYP2C9 genes with the clinical efficacy of oral piroxicam (20 mg daily for 4 days) after lower third molar surgeries with regard to postoperative pain, swelling, trismus, adverse reactions, need for rescue medication and the volunteer’s overall satisfaction.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
11
0
3
Order By: Relevance
“…In addition, in comparison with other studies by our study group evaluating different NSAIDs in bilateral third molar extraction model, ketoprofen 200 mg + omeprazole 20 mg b.i.d. showed as good pain control as other drugs evaluated such as piroxicam, valdecoxib, etoricoxib, meloxicam, ketorolac, naproxen (1,2,8,9,21).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, in comparison with other studies by our study group evaluating different NSAIDs in bilateral third molar extraction model, ketoprofen 200 mg + omeprazole 20 mg b.i.d. showed as good pain control as other drugs evaluated such as piroxicam, valdecoxib, etoricoxib, meloxicam, ketorolac, naproxen (1,2,8,9,21).…”
Section: Discussionmentioning
confidence: 89%
“…had a superior analgesic effect when compared to ketoprofen 100 mg b.i.d., with a statistically significant difference in the control of pain, mainly in the periods of 1.5, 7, 8, 10, 12, 16, 24, 48 and 72 h postoperative. It is worth emphasizing at this moment that the acute pain control after the surgeries by both drugs was effective, since the literature reports that pain below 45 mm does not affect the daily routine of the volunteers (17,21,24). The efficacy of ketoprofen 100 mg has also been compared with methylprednisolone in pain control after third molar surgery, with peak pain intensity occurring within the first 12 h with the use of both drugs (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGx studies of CYP2C9 , not related to anticoagulants, explored associations with the antimalarial effect of chloroquine/primaquine therapy and the efficacy of piroxicam for post‐operative pain, with negative results in both cases.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Nonsteroidal anti-in ammatory drugs (NSAIDs) are mostly used during the postoperative period of third molar surgeries due to their considerable anti-nociceptive effects. [10][11][12] However, recent studies have demonstrated that the preemptive combination of NSAIDs and corticosteroids seems to improve the relief of postoperative symptoms after third molar surgeries, mainly in the acute postoperative period. [4,13,14] A possible explanation for the e cacy of this combination is that when administered before surgical trauma and the onset of pain, the drugs will be present in the bloodstream at the appropriate levels, and at the appropriate time when pain symptoms begin, and the inhibition of cyclooxygenase decreases the production of prostaglandins and other in ammatory cytokines at the surgical site.…”
Section: Introductionmentioning
confidence: 99%